2010
DOI: 10.1111/j.1365-2850.2009.01487.x
|View full text |Cite
|
Sign up to set email alerts
|

Electroconvulsive therapy: a comparison of knowledge and attitudes of student nurses and staff mental health nurses at a psychiatric hospital in Nigeria

Abstract: Electroconvulsive therapy (ECT) is effective in the treatment of some psychiatric disorders. Among other reasons, service users may refuse ECT when indicated due to myth and little or lack of knowledge about the procedure. The knowledge of and attitude towards ECT among nurses may reflect on patients and influence treatment choice. Previous studies, conducted in developed countries have explored knowledge and attitudes towards ECT among nurses, but none have been conducted in this part of the world. The follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 12 publications
1
7
0
Order By: Relevance
“…Many of the students suggested that the procedure should however be guided by legislation in Nigeria. This has also been documented in a similar study conducted recently among staff mental health nurses and student nurses [12].…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Many of the students suggested that the procedure should however be guided by legislation in Nigeria. This has also been documented in a similar study conducted recently among staff mental health nurses and student nurses [12].…”
Section: Discussionsupporting
confidence: 79%
“…It had been observed that knowledge and attitude scores were higher among staff mental health nurses compared to student mental health nurses. More years of experience significantly correlated with higher level of knowledge and positive attitudes among staff mental health nurses [12]. Majority of the respondents believed that ECT was beneficial to the patients but was overused and suggested that there should be guidelines for its use in Nigeria.…”
Section: Introductionmentioning
confidence: 94%
“…[ 9 ] Another study from the same country evaluated the knowledge of and attitude toward ECT of medical students at the time of completion of an 8-week clinical rotation in psychiatry and reported that most of the students had positive attitude toward ECT. [ 10 ] Although there are many studies from India, evaluating the knowledge and attitude of patients and their relatives toward ECT,[ 3 4 ] there is a lack of data on medical professionals.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, all still held negative attitudes [9]. Furthermore, in Nigeria, almost three-quarters of psychiatric nurses believed that ECT was helpful for most psychiatric patients [15]. A recent study found that neurologists and family practitioners needed to have more knowledge of ECT [7].…”
Section: Introductionmentioning
confidence: 99%